Physiologically based pharmacokinetic model for CAR-T cell delivery and efficacy in solid tumors - Andreas G. Hadjigeorgiou; Lance L. Munn; Triantafyllos Stylianopoulos; Rakesh K. Jain (Proceedings of the National Academy of Sciences, 2025)
Abnormal blood vessels limit the delivery and function of endogenous T cells as well as adoptively transferred Chimeric Antigen Receptor (CAR)-T cells in tumor microenvironment (TME). We recently showed that vascular normalization using anti-VEGF therapy can overcome these challenges and improve the outcome of CAR-T therapy in glioblastoma models in mice. Here, we developed a physiologically based pharmacokinetic model to simulate the dynamics of both adoptively transferred CAR-T cells and endogenous immune cells in solid tumors following vascular normalization. Similar to our data, our model simulations show that vascular normalization reprograms the TME from immunosuppressive to immunosupportive by enhancing infiltration of endogenous CD8 + T cells and CAR-T cells, increasing M1 macrophages, and reducing M2 macrophages and regulatory T cells, thereby improving efficacy. Strikingly, vascular normalization reduces the number of infused CAR-T cells needed for tumor control by approximately fivefold. Moreover, synchronizing a second CAR-T infusion at their peak proliferative phase maximizes antitumor function. Furthermore, the efficacy of CAR-T cells engineered to secrete anti-VEGF antibody depends on the ability of CAR-T cells to induce vascular normalization. Additionally, combining vascular and stromal normalization can improve the efficacy of anti-VEGF antibody-producing Fibroblast Activated Protein-CAR-T cells for the treatment of desmoplastic tumors such as pancreatic ductal adenocarcinoma. Finally, the model predicts that local CAR-T delivery can sustain high concentrations within the TME and induce recruitment of other antitumor immune cells, improving outcomes. Our model provides a versatile framework to optimize dosing strategies, treatment sequencing, and delivery routes for improving CAR-T therapies for solid tumors.